89 Do Corticosteroid and Local Anaesthetic Hip Injections Administered Proximal or Distal to The Zona Orbicularis Have an Effect on Patient Satisfaction?. (12th October 2021) - Watts, A; Watkinson, W; Shaw, D
Abstract: Aim: Pubofemoral and ischiofemoral ligaments blend to make zona orbicularis. Zonaorbicularis has been suggested to force fluid from peripheral compartment to central compartment in unidirectional flow. This study aims to assess whether injection of corticosteroid with local anaesthetic injected either proximal or distal to the zona orbicularis has effect on patient satisfaction. Method: This retrospective study investigated consecutive patients undergoing ultrasound guided hip injections at a single centre in the UK between November 2018 and March 2019. Patients were identified using IMPAX© picture archiving and communications system. Radiographs were assessed to see if radiopaque dye and therefore corticosteroid and local anaesthetic had been injected proximal or distal to the zona orbicularis. Clinic letters were accessed on the electronic patient record and we recorded whether patients had pain relief at 24 hours and 2 weeks following hip injection. Results: 133 Patients were identified during the study period, of which 40 were included. At 24 hours post-injection 72% of patients were satisfied and 28% were unsatisfied, for which there was 76% and 70% satisfaction for proximal and distal injections respectively (p = 0.63). At 2 weeks post-injection 45% of patients were satisfied and 55% of patients unsatisfied, for which there was 47% and 44% satisfaction for proximal and distal injections respectively (p = 0.9). Conclusions: Overall patient satisfaction is high following hip corticosteroid and local anaesthetic injection. No difference was found between injections proximal and distal to the zona orbicularis. Further research is needed to quantify the association between proximal and distal injections.